A leucine-rich diet modulates the mTOR cell signalling pathway in the gastrocnemius muscle under different Walker-256 tumour growth conditions - Cruz, Bread (BMC Cancer, 2019)
BACKGROUND: The exact signalling mechanism of the mTOR complex remains a subject of constant debate, even with some evidence that amino acids participate in the same pathway as used for insulin signalling during protein synthesis. Therefore, this work conducted further study of the actions of amino acids, especially leucine, in vivo, in an experimental model of cachexia. We analysed the effects of a leucine-rich diet on the signalling pathway of protein synthesis in muscle during a tumour growth time-course. METHODS: Wistar rats were distributed into groups based on Walker-256 tumour implant and subjected to a leucine-rich diet and euthanised at three different time points following tumour development (the 7th, 14th and 21st day). We assessed the mTOR pathway key-proteins in gastrocnemius muscle, such as RAG-A-GTPase, ERK/MAP4K3, PKB/Akt, mTOR, p70S6K1, Jnk, IRS-1, STAT3, and STAT6 comparing among the experimental groups. Serum WF (proteolysis-induced factor like from Walker-256 tumour) and muscle protein synthesis and degradation were assessed. RESULTS: The tumour-bearing group had increased serum WF content, and the skeletal-muscle showed a reduction in IRS-1 and RAG activation, increased PKB/Akt and Erk/MAP4K3 on the 21st day, and maintenance of p70S6K1, associated with increases in muscle STAT-3 and STAT-6 levels in these tumour-bearing rats. CONCLUSION: Meanwhile, the leucine-rich diet modulated key steps of the mTOR pathway by triggering the increased activation of RAG and mTOR and maintaining JNK, STAT-3 and STAT-6 levels in muscle, leading to an increased muscle protein synthesis, reducing the degradation during tumour evolution in a host, minimising the cancer-induced damages in the cachectic state.